Advances in Understanding the Role of NRF2 in Liver Pathophysiology and Its Relationship with Hepatic-Specific Cyclooxygenase-2 Expression - Marina Fuertes-Agudo; María Luque-Tévar; Carme Cucarella; Paloma Martín-Sanz; Marta Casado (Antioxidants, 2023)
Oxidative stress and inflammation play an important role in the pathophysiological changes of liver diseases. Nuclear factor erythroid 2-related factor 2 (NRF2) is a transcription factor that positively regulates the basal and inducible expression of a large battery of cytoprotective genes, thus playing a key role in protecting against oxidative damage. Cyclooxygenase-2 (COX-2) is a key enzyme in prostaglandin biosynthesis. Its expression has always been associated with the induction of inflammation, but we have shown that, in addition to possessing other benefits, the constitutive expression of COX-2 in hepatocytes is beneficial in reducing inflammation and oxidative stress in multiple liver diseases. In this review, we summarized the role of NRF2 as a main agent in the resolution of oxidative stress, the crucial role of NRF2 signaling pathways during the development of chronic liver diseases, and, finally we related its action to that of COX-2, where it appears to operate as its partner in providing a hepatoprotective effect.